The land of hidden men - Burroughs, Edgar Rice, 1875-1950; Krenkel, Roy G., 1918-1983 (Salt Lake City, UT : Project Gutenberg, 2023)
"The Land of Hidden Men" by Edgar Rice Burroughs is a novel written in 1929 and first published in 1932. Set deep in the jungles of Cambodia, the story unfolds in a forgotten kingdom cut off from the modern world. Burroughs transports readers to an exotic realm where ancient traditions persist and danger lurks in the dense wilderness. Originally serialized as "The Land of Hidden Men" before being published in book form as "Jungle Girl," this adventure tale delivers the author's signature blend of exploration and mystery. (This is an automatically generated summary.)
Original title: Jungle girl
Wikipedia page on this work: https://en.wikipedia.org/wiki/Jungle_Girl_(novel)
Release date is 2023-04-12
Greg Weeks, Mary Meehan and the Online Distributed Proofreading Team at http://www.pgdp.net
Keywords: Jungles -- Fiction; Adventure stories; Explorers -- Fiction; Cambodia -- Fiction